The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1007/s10549-019-05520-5
|View full text |Cite
|
Sign up to set email alerts
|

Axillary management for young women with breast cancer varies between patients electing breast-conservation therapy or mastectomy

Abstract: Purpose-Axillary treatment strategies for the young woman with early-stage, clinically nodenegative breast cancer undergoing upfront surgery found to have 1-3 positive sentinel lymph nodes (SLNs) differ significantly after BCT and mastectomy. Here we compare axillary lymph node dissection (ALND) and regional nodal irradiation (NRI) rates between women electing breast-conservation therapy (BCT) versus mastectomy.Terms of use and reuse: academic research for non-commercial purposes, see here for full terms. http… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“… 14 , 15 It seems that surgeons are more reserved in omitting ALND in young patients with an aggressive tumor subtype, albeit that a recent study suggests that clinicians may forego ALND in young patients when PMRT will be administered. 20 Furthermore, the results of our study showed that patients who undergo adjuvant chemotherapy also were more likely to receive ALND. The higher likelihood of macrometastatic disease or high-grade disease in patients undergoing adjuvant chemotherapy probably contributes to this correlation, albeit that hospital type and the innovative characteric within a hospital also influences the use of systemic therapies and axillary treatment.…”
Section: Discussionmentioning
confidence: 55%
“… 14 , 15 It seems that surgeons are more reserved in omitting ALND in young patients with an aggressive tumor subtype, albeit that a recent study suggests that clinicians may forego ALND in young patients when PMRT will be administered. 20 Furthermore, the results of our study showed that patients who undergo adjuvant chemotherapy also were more likely to receive ALND. The higher likelihood of macrometastatic disease or high-grade disease in patients undergoing adjuvant chemotherapy probably contributes to this correlation, albeit that hospital type and the innovative characteric within a hospital also influences the use of systemic therapies and axillary treatment.…”
Section: Discussionmentioning
confidence: 55%
“…Colpaert and colleagues found that the primary tumor was an independent prognostic factor while axillary micrometastasis were not, and they proposed that micrometastatic disease somehow primes the immune system, allowing for a more robust response against further tumor invasion. The 5-year overall survival in the study by 7,9 Langer and colleagues was equal in bothgroups.…”
Section: Table 5: Showing Surgical Treatment Options In Ebc Patientsmentioning
confidence: 81%
“…Use of the completion axillary lymph node dissection (ALND) was significantly higher in patients who underwent a mastectomy (144/165, 87%), than in patients who underwent BCS (10/192, 5.2%). Regional nodal irradiation was given to a greater proportion of patients who underwent a mastectomy than BCS (48% vs. 30%, p < 0.01) [ 57 ]. This reflects the adoption of the ACOSOG Z0011 findings into the AYA population and follows a similar trend to the general population with breast cancer [ 81 ].…”
Section: Resultsmentioning
confidence: 99%